2022
DOI: 10.1038/s41598-022-09875-6
|View full text |Cite
|
Sign up to set email alerts
|

A glibenclamide-sensitive TRPM4-mediated component of CA1 excitatory postsynaptic potentials appears in experimental autoimmune encephalomyelitis

Abstract: The transient receptor potential melastatin 4 (TRPM4) channel contributes to disease severity in the murine experimental autoimmune encephalomyelitis (EAE) model of multiple sclerosis and to neuronal cell death in models of excitotoxicity and traumatic brain injury. As TRPM4 is activated by intracellular calcium and conducts monovalent cations, we hypothesized that TRPM4 may contribute to and boost excitatory synaptic transmission in CA1 pyramidal neurons of the hippocampus. Using single-spine calcium imaging … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 52 publications
0
5
0
Order By: Relevance
“…To examine whether Trpm4 is expressed in hilar MC cells, we used RNA scope in situ hybridization for its high sensitivity to detect even low level of expression. Unfortunately, immune-histochemical detection of TRPM4 protein is often controversial in the literature[21]. Using RNA scope in situ hybridization within the hippocampal formation, we found abundant Trpm4 mRNA expression primarily in the hilar region (Figure 1 A-C).…”
Section: Resultsmentioning
confidence: 92%
See 1 more Smart Citation
“…To examine whether Trpm4 is expressed in hilar MC cells, we used RNA scope in situ hybridization for its high sensitivity to detect even low level of expression. Unfortunately, immune-histochemical detection of TRPM4 protein is often controversial in the literature[21]. Using RNA scope in situ hybridization within the hippocampal formation, we found abundant Trpm4 mRNA expression primarily in the hilar region (Figure 1 A-C).…”
Section: Resultsmentioning
confidence: 92%
“…Expression pattern of TRPM4 in the brain is controversial because of the lack of selective antibodies. Several studies suggested the role of TRPM4 in neuronal function on different brain regions including the hippocampus[21][31][32] the prefrontal cortex[33] and the pre-Bötzinger[34] complex however, most of these publications used pharmacological tools with questionable selectivity[25] to investigate TRPM4 function. Recently, two studies proved the expression of Trpm4 in brainstem pacemaker neurons using the ultrasensitive RNAscope in situ hybridization technique[35][36].…”
Section: Discussionmentioning
confidence: 99%
“…To examine whether Trpm4 is expressed in hilar MCs, we used RNAscope in situ hybridization for its high sensitivity to detect even low level of expression. Unfortunately, immune-histochemical detection of TRPM4 protein is often controversial in the literature [ 19 ]. Using RNAscope in situ hybridization within the hippocampal formation, we found abundant Trpm4 mRNA expression primarily in the hilar region (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Expression pattern of TRPM4 in the brain is controversial because of the lack of selective antibodies. Several studies suggested the role of TRPM4 in neuronal function on different brain regions including the hippocampus [ 19 , 30 , 31 ], the prefrontal cortex [ 32 ], and the pre-Bötzinger [ 33 ] complex; however, most of these publications used pharmacological tools with questionable selectivity [ 24 ] to investigate TRPM4 function. Recently, two studies proved the expression of Trpm4 in brainstem pacemaker neurons using the ultrasensitive RNAscope in situ hybridization technique [ 34 , 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…Mechanisms of altered excitability are often shared between cardiomyocytes and CNS neurons (Halvorsen et al., 2021). In CNS neurons, TRPM4 is involved in specific types of hippocampal synaptic plasticity and learning, but also glutamate cytotoxicity (Fearey et al., 2022; Gerzanich et al., 2009; Schattling et al., 2012; Simard & Gerzanich, 2018). In vitro experiments in hippocampal slices have reported a lack of long‐term potentiation (LTP) in Trpm4 −/− mice (Bovet‐Carmona et al., 2018, 2019; Menigoz et al., 2016).…”
Section: Introductionmentioning
confidence: 99%